Minimally invasive closure of a progressive pseudoaneurysm of the ascending aorta: A case report - Wu, Yuan; Fan, Linglin; Liu, Fei; Zhuang, Hui; Wu, Xijie (Frontiers in Cardiovascular Medicine, 2023)
Ascending aortic pseudoaneurysm (AAP) are rare but may cause life-threatening complications. Although some cases adopted placement of a stent graft, occluder devices and vascular plugs to exclude the pseudoaneurysm, however, the management of progressive pseudoaneurysms that may rupture at any time is still a challenge that needs to be addressed. In this case, we present an AAP that caused by aortic and mitral valve replacement for giant left ventricle. Aortic pseudoaneurysm was suspected based on a spherical cystic echo (70 × 80mm) of the ascending aorta which was detected by ultrasonic cardiogram, and the diagnosis was confirmed by an aortic computed tomograph angiography (CTA) examination. To prevent the unexpected rupture of a progressive pseudoaneurysm, our patient was performed with 28 mm ASD occluder without any procedural complication. Our patients have a good prognosis, which will inspire clinicians to choose minimally invasive procedure when dealing with such high-risk cases in an emergency.